Platon ve Aristoteles'in sanat etiği, estetik kavramı ve yansımaları - Kavuran, Tamer.; Dede, Bayram. (My University, 2013)
Art and philosophy are the most engaged subjects in the history of humanity. Though many definitions have been made on these two subjects,their meanings have still been discussed even today.These discussions neither have any border nor any dimension,and they will continue as long as humanity exists.Two great philosophers, Platon and Aristotales, extanting from Ancient Greece to today and deeply influencing the philosophy of art, have tried to emphasize the political,social and psychlogical effects of art on society and individual by questioning art for the first time.This questioning has influenced the philosophy of art up today and has formed a landmark.If we want to learn and understand the philosophy of art, we need to know the ideas of Platon and Aristotales on art.If we get away from this landmark,there will be no possibility to understand today’s philosophy of art.The astonishing development of science,daily struggles and a stressful life make the art more needed than ever and make it indispensible for today’s people.It has been Aristotales to examine the positive effects of art on people in a wider scope.Despite this,the architect of this negative approach which makes the art negative in the middle ages, is Platon.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Feısefe; Sanat; Estetik